Proceedings of the 40th International Conference on Software Engineering: Companion Proceeedings 2018
DOI: 10.1145/3183440.3194951
|View full text |Cite
|
Sign up to set email alerts
|

Communication in open-source projects-end of the e-mail era?

Abstract: Communication is essential in software engineering. Especially in distributed open-source teams, communication needs to be supported by channels including mailing lists, forums, issue trackers, and chat systems. Yet, we do not have a clear understanding of which communication channels stakeholders in open-source projects use. In this study, we fill the knowledge gap by investigating a statistically representative sample of 400 GitHub projects. We discover the used communication channels by regular expressions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Following an inductive approach, we wanted to be as openminded as possible. From another study [20], we already knew that projects provide a large variety of channels. Additionally, we wanted to explore any other issue related to communication channels in GitHub projects.…”
Section: Research Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…Following an inductive approach, we wanted to be as openminded as possible. From another study [20], we already knew that projects provide a large variety of channels. Additionally, we wanted to explore any other issue related to communication channels in GitHub projects.…”
Section: Research Objectivementioning
confidence: 99%
“…Additionally, we wanted to explore any other issue related to communication channels in GitHub projects. Käfer et al [20] analyzed communication channels in GitHub projects. They have shown that only half of the analyzed projects use externally visible communication channels.…”
Section: Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Many OSS communities utilize Gitter [31] or Slack [32] as their live communication means. In particular, Gitter is currently the most popular online communication platform [37] since it provides open access to public chat rooms and free access to historical data [49]. Considering the popular, open, and free access nature, we conduct this study based on Gitter 2 .…”
Section: The Gitter Platformmentioning
confidence: 99%
“…The authors argue that the system increased awareness of the software's build status and helped agile teams with self-supervision [19]. In modern software development, chat solutions have disrupted previous software development processes and have replaced email in some cases [9], [20]. Fitzpatrick et al combined the informal discussions developers have about code with version control information reporting code changes in a ticker tape form [21].…”
Section: A Software Engineeringmentioning
confidence: 99%